2021
DOI: 10.1016/j.prosdent.2020.08.013
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 16.9-year survival of pressed acid etched e.max lithium disilicate glass-ceramic complete and partial coverage restorations in posterior teeth: Performance and outcomes as a function of tooth position, age, sex, and thickness of ceramic material

Abstract: Statement of problem. Long-term clinical data are lacking on the comparison of the survival of adhesively luted pressed e.max lithium disilicate glass ceramic complete and partial coverage restorations in posterior dentitions and the effect that different technical and clinical variables have on their survival. Purpose. The purpose of this clinical study was to examine and compare the 16.9-year survival of posterior pressed e.max lithium disilicate glass ceramic complete and partial coverage restorations and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(65 citation statements)
references
References 32 publications
0
59
0
Order By: Relevance
“…Medium-and long-term studies are consistent in confirming that ceramic overlay restorations have an acceptable survival in both cases exceeding 90% [3,14,15,16] . Malament et al indicate in their study a survival rate of 96.49% for 16.9 years, without finding a significant difference with the survival rate of conventional full-coverage crowns [17] . The most frequently reported failure pattern is fracture of the ceramic and/or the tooth (76.2%), followed by decementation (42.9%) and, lastly, due to caries leakage (28.6%) [3] .…”
Section: Survivalmentioning
confidence: 75%
See 2 more Smart Citations
“…Medium-and long-term studies are consistent in confirming that ceramic overlay restorations have an acceptable survival in both cases exceeding 90% [3,14,15,16] . Malament et al indicate in their study a survival rate of 96.49% for 16.9 years, without finding a significant difference with the survival rate of conventional full-coverage crowns [17] . The most frequently reported failure pattern is fracture of the ceramic and/or the tooth (76.2%), followed by decementation (42.9%) and, lastly, due to caries leakage (28.6%) [3] .…”
Section: Survivalmentioning
confidence: 75%
“…However, there are still beliefs to avoid the use of lithium disilicate in the posterior dentition because of the high occlusal loads that could lead to premature fractures. Nevertheless, studies have shown that lithium disilicate adhesive overlay restorations have adequate mechanical behavior under load [2,4,7,10,17,19,20,21,22,23,24,25] . Some authors argue that increasing the thickness of the material is one of the ways to increase its strength, however, this means increased removal of hard tissue, which is sometimes counterproductive.…”
Section: Fracture Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…Long-term clinical data on the survival of pressed lithium disilicate glassceramic restorations and the effect that different technical and clinical variables have on survival are lacking. With this in mind, a series of reports emerging from one private practice [206][207][208] involving a prospective database with controls for clinical and laboratory variables reported on recall findings of a substantial patient population. The purpose of the initial clinical report in this series 206 was to examine the 10-year survival of pressed lithium disilicate glass-ceramic monolithic and bilayer restorations and the relationship between clinical parameters and outcomes.…”
Section: Conventional Fixed Prosthodonticsmentioning
confidence: 99%
“…A third publication originating from the same private prosthodontic practice 208 sought to investigate the 16.9year survival of exclusively posterior pressed lithium disilicate complete and partial coverage restorations and the effects of associated parameters on clinical outcomes. Patients requiring either single-unit posterior partial coverage restorations, complete coverage restorations, or a combination were recruited.…”
Section: Conventional Fixed Prosthodonticsmentioning
confidence: 99%